Tuning the Catalytic Activity of UiO‐66 via Modulated Synthesis: Esterification of Levulinic Acid as a Test Reaction. Issue 10 (26th February 2020) - Wei, Ruiping; Fan, Jingdeng; Qu, Xumin; Gao, Lijing; Wu, Yuanfeng; Zhang, Zongqi; Hu, Feng; Xiao, Guomin
Abstract : Due to their high stabilities and tunable defects, zirconium terephthalate UiO‐66 type metal organic frameworks (MOFs) have been promising catalysts in many catalytic reactions. The catalytic activity of UiO‐66 MOFs is significantly affected by the density of defects and hydroxyl groups bonded to Zr6 nodes, which can be tuned by modulators. In this work, a series of defective UiO‐66 were synthesized via tuning the ratio of H2 BDC/Zr and adding monocarboxylic acids with different chain length as modulators. The synthesized UiO‐66 MOFs were characterized by powder X‐ray diffraction, N2 physisorption, IR and 1 H NMR spectroscopy, scanning and transmission electron microscopy. Esterification of levulinic acid with ethanol was selected to reveal the influence of modulators, defects and hydroxyl groups. The results showed that UiO‐66 with 0.5 of H2 BDC/Zr ratio and lauric acid as the modulator owned excellent catalytic activity. The cooperative effects, between the Lewis acid sites offered by unsaturated Zr6 nodes and Brønsted acid sites supplied by OH, has been revealed to have a significant influence on the catalytic activity. Abstract : Esterification of levulinic acid with ethanol was catalyzed by the cooperative effects between the Lewis acid sites offered by unsaturated Zr6 nodes and Brønsted acid sites supplied by OH in defective UiO‐66 MOFs with high defect density, which was tuned by precursor ratios and modulators.